do you mean something like this: [2(a^10)(b^2)][3(a^2)(b^2)]
if so, then
for constants, we just multiply them normally,, for the variables, recall some laws of exponent,, multiplying terms of same base is also equal to base raised to sum of its exponents,, for example
5^2 * 5^5 = 5^(2+5) = 5^7
x^3 * x^(-4) = x^(3-4) = x^(-1)
thus
for constants: 2*3 = 6
for base a: a^10 * a^2 = a^12
for base b: b^2 * b^2 = b^4
multiplying all of them, we have
6a^12*b^4
hope this helps~ :)
wanted to know if I got the correct answer?
question (2a10b2)(3a2b2)
answer 6a^12+5a^12b^4+b^4
2 answers
one number is 5times anotherand their sum is 438.whatare the number?give answer in part a,b and c